Organocatalytic Asymmetric Vinylogous Aldol Reactions - Bisai, Vishnumaya (Synthesis, 2012)
The aldol reaction is one of the most predominantly used reactions for the formation of C–C bonds in synthetic organic chemistry. The vinylogous extension of this fundamental C–C bond-forming reaction to nucleophilic components, such as the vinylogous aldol reaction is significant because it provides rapid access to polyketide derivatives such as δ-hydroxy-β-keto esters and α,β-unsaturated δ-hydroxy carbonyl compounds. Further transformation of these compounds can be accomplished with good diastereoselectivity and leads the way to polyol units, a motif common to many pharmaceutically important natural products. Details of recent advances in the organocatalytic vinylogous aldol reaction and its applications are discussed in this review.
Keywords: vinylogy; organocatalysis; enantioselective; aldol reactions; vinylogous aldol reactions; vinylogous Mukaiyama aldol reactions; butenolides; polyketides